2013
DOI: 10.5194/nhess-13-2483-2013
|View full text |Cite
|
Sign up to set email alerts
|

Daily precipitation records over mainland Spain and the Balearic Islands

Abstract: Abstract. Understanding the spatial distribution of extreme precipitations is of major interest in order to improve our knowledge of the climate of a region and its relationship with society. These analyses inevitably require the use of directly observed values to account for the actual extreme amounts rather than analyzed gridded values. A study of daily rainfall extremes observed over mainland Spain and the Balearic Islands is performed by using records from 8135 rain gauge stations from the Spanish Weather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…In the Iberian Peninsula there are many studies showing the spatiotemporal variation of rainfall and the availability of water resources (García‐Barrón et al, ; Sánchez et al, ; Estrela et al, ; Guerreiro et al, ; Aguilar‐Alba, ). Other studies have analysed the rainfall variation at daily time scales (Martin‐Vide, ; Rodrigo and Trigo, ; Acero et al, ; Gallego et al, ; Ramis et al, ), or at monthly or seasonal time scales (García et al, ; Ninyerola et al, ; Martínez et al, ; Rodrigo, ; Del Rio et al, ; Costa et al, ; De Lima et al, ). Thus, De Luis et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the Iberian Peninsula there are many studies showing the spatiotemporal variation of rainfall and the availability of water resources (García‐Barrón et al, ; Sánchez et al, ; Estrela et al, ; Guerreiro et al, ; Aguilar‐Alba, ). Other studies have analysed the rainfall variation at daily time scales (Martin‐Vide, ; Rodrigo and Trigo, ; Acero et al, ; Gallego et al, ; Ramis et al, ), or at monthly or seasonal time scales (García et al, ; Ninyerola et al, ; Martínez et al, ; Rodrigo, ; Del Rio et al, ; Costa et al, ; De Lima et al, ). Thus, De Luis et al .…”
Section: Introductionmentioning
confidence: 99%
“…The other centre, located towards the southeast of the Balearic Islands, could not provide feeding flow to the Valencia area, but to the Balearic Islands. Figure 13 makes a comparison between the situation of 28th September 2012 (AROME analysis) and that of 4th November 1987 (manual analysis), the latter with record rainfall of over 800 mm in 24 hours (Ramis et al, 2013). The influence of the particular distribution of depression centres on the distribution of rain has to be determined, and this can be done by numerical experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…The rest of each month was not very productive in terms of heavy rain, especially September. It is of interest that the region that traditionally accumulates stronger rainfall, which is south of Valencia and north of Alicante (Safor and Marina Alta) (Font, 1983;Ramis et al, 2013) showed a deficit this year, particularly in October. Therefore, the most iconic episodes of heavy rainfall were missing, but there was enough variety and abundance of episodes.…”
Section: Climatological Balance Of September and October 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…Historical references to heavy precipitation events are numerous, some of these going back to the Middle Ages (e.g. 1991)., Barceló In this context, the province of Valencia (eastern Spain) possesses one of the highest daily accumulations ever recorded in Europe, 817 mm on 3 November 1987 (Ramis et al , 2013). Two of the greatest flash‐flood‐producing storms in Valencia region during the last decades, associated with circular‐shaped meso‐ β convective systems, were thoroughly analyzed by Romero et al (2000) and Fernández et al (1995) using mesoscale numerical modelling.…”
Section: Introductionmentioning
confidence: 99%